The Effectiveness of Group Counseling with Sfbc And Mindfulness Training Group Approaches to Reduce the Technostress of Students Who Use Smartphone - Munir, Ahmad; Sugiyo, Sugiyo; Mulawarman, Mulawarman (Universitas Negeri Semarang, 2021)
Smartphone presence in today’s era truly advantages students in both learning process and personal business. However, when there is no good time management of smartphone usage, students may experience technostress. Regarding this issue, this study strived to examine the effectiveness of group counseling with SFBC and mindfulness training group approaches to reduce the technostress of students who use smartphone. In its implementation, there were 14 students chosen using random assignment as the samples and divided into two groups with each group consisted of 7 students. For the method, this study used experimental method with randomized pretest-posttest comparison group design. Students’ technostress data were collected using technostress scale and analyzed through Wilcoxon Sign Rank Test and Mann Whitney. It was found that: 1) the group counseling with SFBC approach successfully reduced the students’ technostress in the SFBC experimental group. 2) Mindfulness training group made it to reduce the students’ technostress in mindfulness training group experimental group. 3) the intervention in the SFCB experimental group appeared to be more effective to reduce the technostress of students who use smartphone compared to the mindfulness training group. Thus, it is recommended to apply the group counseling with SFBC approach to reduce the technostress of students who use smartphone.